Emotional intelligence in intellectually handicapped individuals - Trambacz, Sylwia; Gołaska, Paulina (Studia Psychologica: Theoria et praxis, 2010)
According to Salovey’s and Mayer’s theory, emotional intelligence (IE) is understood as an ability to process affective stimulus. A competence to decode mimie expression, which is basie for IE, is thought to be crucial in development of other socio emotional skills and social adaptation. This stu dy was designed to investigate the capability of recognizing emotion from facial expression by persons with intellectual disability. There were 75 par ticipants with mild, moderate and severe mental retardation diagnosis. The average age was 37 (SD=9,6). IE level was measured with Skala Inteligencji Emocjonalnej Twarze (SIE T). The ability to recognize and match facial expressions was significantly dependant on cognitive impairments’ severity. There was no difference among gender or age varied groups. Distinguishing between both facial expressions and emotion seems to be an essential com ponent of mental health and well being. These data demonstrate then the necessity to design and carry out regular emotional expression recognition training for people with intellectual disabilities.